Implementación de la NIC 41 (Agricultura): El caso de una empresa MYPE peruana - Tanaka Nakasone, Gustavo (2023)
The primary purpose of this paper is to present an actual case of a Peruvian SME which applied IFRS accounting standards specifically, IAS 41 for consumable biological assets to reflect its financial situation more accurately as an alternative to legal and tax regulations applying historical cost, which Peruvian SMEs more commonly use for the preparation of financial statements. Primary data were gathered through interviews and observation at the SME studied. This forestry-industry SME in question tried unsuccessfully to get financing from banks, even presenting complementary information regarding the calculation of biological asset values according to IAS 41. Failing this, it turned to seeking funding from private long-term investors, eventually succeding in obtaining long-term financing from a new strategic investor. The significance of this paper is that it presents evidence of the advantages for companies (specifically agriculture-related companies) that comply with IFRS in a country where historical cost-based tax rules are traditionally applied for accounting purposes. Other SMEs can similarly improve the likelihood of obtaining new capital from potential investors by complementing the information provided in financial statements with detailed data regarding fair value calculation of biological assets.